Sporicidal Effect of Peracetic Acid Vapor - Portner, Dorothy M. (1968)
The sporicidal activity of peracetic acid (PAA) vapor at 20, 40, 60, and 80% relative humidity (RH) and 25 C was determined on Bacillus subtilis var. niger spores on paper and glass surfaces. Appreciable activity occurred within 10 min of exposure to 1 mg of PAA per liter and 40% or higher RH. The sporicidal rate decreased from the optimum at 80% RH to a slight effect at 20% RH. Spores on an impermeable surface were more difficult to kill than those on a porous one, probably because the cells tend to pile up on an impermeable surface and the vapor penetrates poorly through the layer of covering cells.